High temperature deformation and fracture of materials - Zhang, Junshan (Woodhead Publishing in materials., 2010)
The energy, petrochemical, aerospace and other industries all require materials able to withstand high temperatures. High temperature strength is defined as the resistance of a material to high temperature deformation and fracture. This important book provides a valuable reference to the main theories of high temperature deformation and fracture and the ways they can be used to predict failure and service life. Analyses creep behaviour of materials, the evolution of dislocation substructures during creep, dislocation motion at elevated temperatures and importantly, recovery-creep theories of pure metalsExamines high temperature fracture, including nucleation of creep cavity, diffusional growth and constrained growth of creep cavitiesA valuable reference to the main theories of high temperature deformation and fracture and the ways they can be used to predict failure and service life.